"Double‐duty" conventional dendritic cells in the amphibian Xenopus as the prototype for antigen presentation to B cells. Issue 3 (14th February 2018) - Neely, Harold R.; Guo, Jacqueline; Flowers, Emily M.; Criscitiello, Michael F.; Flajnik, Martin F.
Abstract: Two populations of dendritic cells (DCs) are found in mammals, one derived from hematopoietic precursors (conventional/cDC), and another derived from mesenchymal precursors, the follicular DC (FDC); the latter is specialized for antigen presentation to B cells, and has only been definitively demonstrated in mammals. Both cDC and FDC are necessary for induction of germinal centers (GC) and GC‐dependent class switch recombination (CSR) and somatic hypermutation (SHM). We demonstrate that in Xenopus, an amphibian in which immunoglobulin CSR and SHM occur without GC formation, a single type of DC has properties of both cDC and FDC, including high expression of MHC class II for the former and display of native antigen at the cell surface for the latter. Our data confirm that the advent of FDC functionality preceded emergence of bona fide FDC, which was in turn crucial for the development of GC formation and efficient affinity maturation in mammals. Abstract : Thymus‐dependent immunization of Xenopus induces the migration and reorganization of conventional dendritic cells to the internal perimeter of the splenic white pulp, where they perform the functions of mammalian follicular dendritic cells: presenting native antigen to B cells, while producing chemoattractant and pro‐survival cytokines.